О линьке серого журавля в Юго-Восточной Украине - Винтер, С.В.; Горлов, П.И.; Шевцов, А.А. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2016)
При многолетних наблюдениях серого журавля на южной границе гнездового ареала (Днепропетровская, Харьковская и Луганская обл.; 1989-2013 гг.) и южнее его, в степной зоне Юго-Восточной Украины (Керченский п-ов Крыма и Сиваш; 1985-1991 гг.), для изучения линьки собраны и определены (по эталонной коллекции Питомника редких журавлей Окского заповедника) 2676 перьев этого вида. Під час багаторічних досліджень сірого журавля на південній межі гніздового ареалу (Дніпропетровська, Харківська та Луганська обл., 1989-2013 рр.) та південніше в степовій зоні Пiвденно-Схiдної України (Керченський п-ів Криму та Сиваш; 1985-1991 рр.) для вивчення линьки зібрані та визначені за допомогою еталонної колекції Розплідника рідкісних журавлів Окського заповідника 2676 пір’їн цього виду. In the course of long-term observations of Common Cranes at the southern border of their breeding range (Dnipropetrovsk, Kharkiv, and Luhansk regions, 1989-2013) and further south, in the steppe zone of South-Eastern Ukraine (Kerch Peninsula of the Crimea and Syvash, 1985-1991), a total of 2,676 feathers were collected and identified to study the moult of the species. The reference specimens from the collection of the nursery of rare crane species at Oksky State Nature Biosphere Reserve, Russia were used.